Fourier Transform To Explain The Process Of Computed Tomography - Chávez Ramírez, Edwin (2017)
Computed tomography (CT) is a breakthrough technology used in medicine for diagnostic diseases. The same technique is used in other areas, such as aerospace chemistry, Radio astronomy, etc. The main objective of the CT is to reconstruct the internal part of an object without having to open it as a non-destructive test. To achieve this purpose, the CT uses the attention that X-rays undergo through this object with the information, the inner part of the object is reconstructed, that is to say the CT is an inverse problem.In this article uses the Fourier transform for the reconstruction of the internal part, for it is directly part of a continuous model, representing the density at the point (x, y) of a section, with a function p = p(x, y); and even though p is not required to be continuous, the Fourier method is more efficient and a better, more regular result is obtained p.